1958
DOI: 10.1161/01.res.6.5.624
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Atrial and Ventricular Tachycardia on Cardiac Output, Coronary Blood Flow and Mean Arterial Blood Pressure

Abstract: The effect of electrically induced auricular and ventricular tachycardia of various rates was studied in the anesthetized dog. When, the control heart ranging between 140 and 190 per minute, atrial tachycardia of a rate only slightly higher than the control rate was induced, a very temporary initial decrease in arterial blood pressure, cardiac output and coronary blood flow occurred, then all three parameters essentially returned to control level. With atrial tachycardia of a higher rate, blood pressure, cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1966
1966
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 10 publications
2
18
0
Order By: Relevance
“…However, the changes in rate were less in the present study than in those studies which demonstrate a clear relation between coronary flow and heart rate (49,50). The failure to find any significant change in the coronary blood flow after conversion of atrial fibrillation to sinus rhythm is compatible with the results of Wegria who demonstrated in the open-chest dog that electrically induced atrial or ventricular tachycardias usually produced no change or a slight increase in the coronary blood flow (51,52). Corday, Gold, DeVera, Williams, and Fields, however, believed that a decrease in the systemic blood pressure associated with tachycardias resulted in a decrease in coronary blood flow (53).…”
Section: Resultssupporting
confidence: 84%
“…However, the changes in rate were less in the present study than in those studies which demonstrate a clear relation between coronary flow and heart rate (49,50). The failure to find any significant change in the coronary blood flow after conversion of atrial fibrillation to sinus rhythm is compatible with the results of Wegria who demonstrated in the open-chest dog that electrically induced atrial or ventricular tachycardias usually produced no change or a slight increase in the coronary blood flow (51,52). Corday, Gold, DeVera, Williams, and Fields, however, believed that a decrease in the systemic blood pressure associated with tachycardias resulted in a decrease in coronary blood flow (53).…”
Section: Resultssupporting
confidence: 84%
“…Previous reports have consistently demonstrated a marked augmentation of coronary blood flow by rapid heart rates in both atrial and ventricular pacing (Wegria et al 1958;Maxwell et al 1958;Pitt and Gregg 1968;Cobb et al 1969). …”
Section: Discussionmentioning
confidence: 87%
“…The data suggest that the coronary circulation would be affected by ventricular pacing because of the decreased perfusion pressure. However, there have been few reports as to whether the pacemaking site of the ventricle influence the coronary circulation (Wegria et al 1958;Badeer and Feisal 1965;Bache et al 1970). It has been well known that the coronary circulation normally responds to increased myocardial oxygen demand with an increase of coronary blood flow (Eckenhoff et al 1947).…”
mentioning
confidence: 99%
“…Wiggers (1954) would again contradict this view, claiming that tachycardia increases coronary flow by a massaging effect. Furthermore, tachycardia in the intact heart also improves the coronary flow because of an increased cardiac output (W6gria, Frank, Wang & Lammerant, 1958;Lewis, Coffman & Gregg, 1961). Catecholamines therefore appear to cause an initial resistance to coronary perfusion, firstly by a direct vasoconstriction mediated by a-adrenoceptors and secondly due to extravascular compression during the rate and force increases.…”
Section: Discussionmentioning
confidence: 99%